-14+5k=k-3k

Simple and best practice solution for -14+5k=k-3k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -14+5k=k-3k equation:


Simplifying
-14 + 5k = k + -3k

Combine like terms: k + -3k = -2k
-14 + 5k = -2k

Solving
-14 + 5k = -2k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '2k' to each side of the equation.
-14 + 5k + 2k = -2k + 2k

Combine like terms: 5k + 2k = 7k
-14 + 7k = -2k + 2k

Combine like terms: -2k + 2k = 0
-14 + 7k = 0

Add '14' to each side of the equation.
-14 + 14 + 7k = 0 + 14

Combine like terms: -14 + 14 = 0
0 + 7k = 0 + 14
7k = 0 + 14

Combine like terms: 0 + 14 = 14
7k = 14

Divide each side by '7'.
k = 2

Simplifying
k = 2

See similar equations:

| 3m+6+6=m-18 | | -99=-3(3x+7)-6 | | 2(s-6)=4 | | 9y-y=-14+y | | (2x)+16=48 | | C+c+3=53 | | (8x+5)+(4x-5)=180 | | 2(-5)+y=6 | | C-7=5.3 | | 15-2/3x=9 | | y-9=6/7(x-4) | | ln(a+10)+5=7 | | (1-3)x+5=6x+-8 | | 2x+5+3x+10=100 | | 3.5h=2h-12 | | 10(4x+2)=3(8-x)+6 | | 8x+5+4x-5=180 | | y-9=6/7)x-4) | | 0.83t^2-10t+31=0 | | 2n+11=10 | | -14=7(y-5) | | -2=7-v | | 7-2a=54 | | 10+e-5+e=5(e-1) | | -7/2-3/7x=-8/3 | | 4x^2=-28x | | 3(u+6)=7u | | 9y-8y=12 | | x-4-1=7 | | 2x^2+13x-30=0 | | 4(13n+4)=-36 | | 3u+30=-3(u+6) |

Equations solver categories